Microstructural evolution of high-nickel steel during quenching, lamellarizing, and tempering heat treatment - Guojin Sun; Qi Wang; Zhenggui Li (Journal of Materials Research and Technology)
To investigate the influence of Quenching, Lamellarizing and Tempering (QLT) heat treatment processes on the microstructural evolution of nickel alloyed steel, samples were subjected to quenching at 870 °C, followed by Lamellarizing from 720 °C to 780 °C, and tempering at 580 °C. The results indicate that the QLT treatment produces a multiphase microstructure consisting of tempered martensite and stabilized retained austenite. Lamellarizing at 770 °C produced a more uniform microstructure with reduced low-angle grain boundaries compared to 720 °C. Energy-dispersive spectroscopy (EDS) identified higher alloy element concentrations in retained austenite, contributing to its stability and enhancing low-temperature toughness. The results demonstrate that QLT heat treatment effectively modifies the microstructural characteristics and mechanical properties, offering a method to optimize material performance for specific applications.